(untitled) (Indonesian Health Justice Review, 2024)
Access to essential medicines is a fundamental human right and a critical aspect of health justice. This paper explores the legal frameworks in Indonesia that govern the availability, affordability, and distribution of essential medicines, focusing on the barriers faced by underserved populations. The study analyzes the current regulatory policies, including the national essential medicines list (NEML), and assesses how effectively these laws ensure access to life-saving drugs, particularly in rural and remote regions. Through a combination of legal analysis, interviews with policymakers, healthcare providers, and patients, the research identifies gaps in the legal system, including regulatory inefficiencies, pricing barriers, and distribution challenges. Findings suggest that while Indonesia has made progress in expanding access to medicines, significant disparities remain, with low-income populations and those in remote areas still unable to obtain critical medications. The paper advocates for strengthening Indonesia’s legal framework by revising pricing policies, improving supply chain management, and enhancing the enforcement of access laws. The study concludes that ensuring equitable access to essential medicines requires both legal reforms and comprehensive public health strategies.